Nutritious effects of nostoc (cushuro) in the undernourished children of 1 to 3 years of the district of Amarilis -2007 - Villavicencio Guardia, Maria (2016)
The study aimed to determine the effectiveness of nostoc sp in children 1 to 3 years Amarilis District 2007, province and department of Huanuco. The research was experimental and intervention, longitudinal and prospective, the sample is up to 20 children from 1 to 3 years, divided into two experimental groups and control. To collect information using a structured form, using tables Waterlow It assessed the nutritional status. The results were significant, complementary food based Nostoc improving the nutritional status of children and the value of calculated t statistic = 3.096, and the level of significance for our study was 0.05. Also worth noting that before the children of 1 years of age to 5% had mild and AFTER 5% of children in this age of nutritional status is normal. In children 2 years of age before 25% mild, and then in 15% of normal children of their nutritional status and 5% were overweight. In children 3 years old before the 20% were mild, and then in 15% of their nutritional status is normal.